Potential impact of climate and socioeconomic changes on future agricultural land use in West Africa - Ahmed, K. F.; Wang, G.; You, Liangzhi; Yu, M. (Copernicus GmbH, 2016)
Abstract. Agriculture is a key component of anthropogenic land use and land cover changes that influence regional climate. Meanwhile, in addition to socioeconomic drivers, climate is another important factor shaping agricultural land use. In this study, we compare the contributions of climate change and socioeconomic development to potential future changes of agricultural land use in West Africa using a prototype land use projection (LandPro) algorithm. The algorithm is based on a balance between food supply and demand, and accounts for the impact of socioeconomic drivers on the demand side and the impact of climate-induced crop yield changes on the supply side. The impact of human decision-making on land use is explicitly considered through multiple "what-if" scenarios. In the application to West Africa, future crop yield changes were simulated by a process-based crop model driven with future climate projections from a regional climate model, and future changes of food demand is projected using a model for policy analysis of agricultural commodities and trade. Without agricultural intensification, the climate-induced decrease in crop yield together with future increases in food demand is found to cause a significant increase in cropland areas at the expense of forest and grassland by the mid-century. The increase in agricultural land use is primarily climate-driven in the western part of West Africa and socioeconomically driven in the eastern part. Analysis of results from multiple scenarios of crop area allocation suggests that human adaptation characterized by science-informed decision-making can potentially minimize future land use changes in many parts of the region.